Factors affecting formation of deethyl and deisopropyl products from atrazine degradation in UV/H2O2 and UV/PDS. Issue 46 (5th June 2017) - Luo, Congwei; Jiang, Jin; Guan, Chaoting; Ma, Jun; Pang, Suyan; Song, Yang; Yang, Yi; Zhang, Jianqiao; Wu, Daoji; Guan, Yinghong
Abstract : Formation of deethyl products (DEPs) ( i.e., atrazine amide and deethylatrazine) and deisopropyl product ( i.e., deisopropylatrazine (DIA)) from parent atrazine (ATZ) degraded in UV/H2 O2 and UV/PDS processes under various conditions was monitored. Abstract : In this study, the formation of deethyl products (DEPs) ( i.e., atrazine amide (Atra-imine) and deethylatrazine (DEA)) and deisopropyl product ( i.e., deisopropylatrazine (DIA)) from parent atrazine (ATZ) degraded in UV/H2 O2 and UV/PDS processes under various conditions was monitored. It was found that SO4 ˙ − displayed a more distinctive preference to the ethyl function group of ATZ than HO˙, leading to the higher ratio of DEPs/DIA in UV/PDS system than that in UV/H2 O2 system in pure water. The effects of water matrices ( i.e., natural organic matter (NOM), carbonate/bicarbonate (HCO3 − /CO3 2− ), and chloride ions (Cl − )) on ATZ degradation as well as formation of DEPs and DIA were evaluated in detail. The degradation of ATZ by UV/PDS was significantly inhibited in the presence of NOM, HCO3 − /CO3 2− or Cl −, because these components could competitively react with SO4 ˙ − and/or HO˙ to generate lower reactive secondary radicals ( i.e., organic radicals, carbonate radicals (CO3 ˙ − ) or reactive chlorine radicals (RCs)). The yields of these DEPs and DIA products from ATZ degradation were not impacted by NOM or HCO3 − /CO3 2−, possibly due to the low reactivity of organic radicals and CO3 ˙ − toward the side groups of ATZ. Howbeit, the increase of DIA yield companied with the decrease of DEPs yield was interestingly observed in the presence of Cl −, which was attributed to the promotion of Cl − at moderate concentration (mM range) for the conversion of SO4 ˙ − into HO˙. Comparatively, in the UV/H2 O2 process, NOM and HCO3 − /CO3 2− exhibited a similar inhibitory effect on ATZ degradation, while the influence of Cl − was negligible. Differing from UV/PDS system, all these factors did not change DEPs and DIA yields in UV/H2 O2 process. Moreover, it was confirmed that RCs had a greater selectivity but a lower reactivity on attacking the ethyl function group than that of SO4 ˙ − . These findings were also confirmed by monitoring the degradation of ATZ as well as the formation of DEPs and DIA in three natural waters.